2018
DOI: 10.4103/abr.abr_277_16
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxybutyrate)/chitosan Aligned Electrospun Scaffold as a Novel Substrate for Nerve Tissue Engineering

Abstract: Background:Reconstruction of nervous system is a great challenge in the therapeutic medical field. Nerve tissue engineering is a novel method to regenerate nervous system in human health care. Tissue engineering has introduced novel approaches to promote and guide peripheral nerve regeneration using submicron and nanoscale fibrous scaffolds.Materials and Methods:In this study, 9 wt% poly(3-hydroxybutyrate) (PHB) solutions with two different ratios of chitosan (CTS) (15%, and 20%) were mixed in trifluoroacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Contact angle measurements carried out on aligned and random electrospun PHB/CTS revealed that the fibrous scaffolds containing CTS were more hydrophilic than the pure fibers and that the aligned fibers had a lower WCA than random scaffolds. The WCAs of PHB, PHB/15 wt% CTS and PHB/20 wt% CTS are 124°, 62°, 43° for random fibers and 110°, 54°, 43° for aligned electrospun fibers, respectively [ 52 ]. Other works have reported that the addition of CTS improves the hydrophilicity of PHAs [ 53 , 54 , 55 ].…”
Section: The Most Important Properties Of the Hybrids Based On Phasmentioning
confidence: 99%
“…Contact angle measurements carried out on aligned and random electrospun PHB/CTS revealed that the fibrous scaffolds containing CTS were more hydrophilic than the pure fibers and that the aligned fibers had a lower WCA than random scaffolds. The WCAs of PHB, PHB/15 wt% CTS and PHB/20 wt% CTS are 124°, 62°, 43° for random fibers and 110°, 54°, 43° for aligned electrospun fibers, respectively [ 52 ]. Other works have reported that the addition of CTS improves the hydrophilicity of PHAs [ 53 , 54 , 55 ].…”
Section: The Most Important Properties Of the Hybrids Based On Phasmentioning
confidence: 99%
“…Other studies indicated that hMSCs were able to preferentially differentiate in the presence of aligned fiber patterns, with effects on cell-cell communication through gap junctions [27]. A key aspect concerns cell interaction of cells with aligned fibers and the contribution of mechanical properties of aligned fiber pattern on cell response in comparison with random fibers [35]. Several studies have not surprisingly reported about the improvement of mechanical response (i.e., tensile, flexural) of aligned fibers with respect to random ones, due to the macroscopic (i.e., higher physical interactions and fiber packing) and microscopic (i.e, higher crystallinity) properties induced by the basic principle of electrospinning process.…”
Section: Fiber Alignmentmentioning
confidence: 99%
“…Several studies have not surprisingly reported about the improvement of mechanical response (i.e., tensile, flexural) of aligned fibers with respect to random ones, due to the macroscopic (i.e., higher physical interactions and fiber packing) and microscopic (i.e., higher crystallinity) properties induced by the basic principle of electrospinning process. Aligned fibers can be variously assembled to form anisotropic structures with heterogeneous tensile properties along different ways, i.e., differences of over one order of magnitude in the elastic modulus from 0 • to 90 • orientation angles with respect to the applied load direction, thus providing a selective transfer of biomechanical stimuli to cells as required for the repair of tissues as tendon, nerve, skin, and bone, as well as cartilage [35][36][37]. It is well known that the actin cytoskeleton of cells follows the aligned pattern of fibers and helps cells to recover from stretch during mechanical loading [38].…”
Section: Fiber Alignmentmentioning
confidence: 99%
“…Consequently, electrospun biomaterials have found applications in various fields including tissue engineering and regenerative medicine. 25 A variety of biomaterial scaffolds fabricated by electrospinning PHB with various blends have been reported, and their potential for applications in engineering of bone, 26 , 27 cartilage, 28 nerve, 29 retinal, 30 and muscle tissues 31 among others have been explored. While PHB scaffold morphology and function are influenced by copolymerizing and blending, Wang et al have reported that fiber diameter and pore size in electrospun PHB matrices can also be significantly altered by changes to fabrication parameters, including temperature, voltage, polymer concentration, and distance from the collector plate.…”
Section: Introductionmentioning
confidence: 99%